A review on protection challenges in microgrids - Miveh, M. R.; Gandomkar, M.; Mirsaeidi, S.; Gharibdoost, M. R. (2012 Proceedings of 17th Conference on Electrical Power Distribution Networks, 2012)
Microgrids are becoming increasingly attractive to consumers and in the near future, a great number of them will be installed in consumer's sites. Microgrids can operate in both grid connected and islanded modes and make use of DG (Distributed Generation) technologies such as micro-turbine, fuel cell, photo voltaic system together with storage devices such as battery, condenser and flywheel. Introduction of microgrids has been accompanied with considerable challenges. Protection of distributed system in the presence of microgrids is one of them. The presence of microgrid not only does change the load flow of the network, but also influences fault currents. The present paper reviews protection problems resulting from microgrid's presence in distribution system and presents a classification of protection schemes.